Uruchamianie pamięci osobistej w epistolarnych ujęciach literatury dziecięcej - Niesporek-Szamburska, Bernadeta (Stylistyka, 2020)
At the beginning of her article, the author briefly presents the assumptions of memorystudies. She indicates that literature and written forms create some kind of “traces” of memory and shows, among written genres, the letter as a genre particu- larly associated with life and as an auto-narrative personal document. The use of the letter genre in the function of a special medium activating the personal memory of the intra-textual recipient in literature for children and adolescents is the subject of further analysis. In two novels for youth: “Dziewczyna z pomarańczami” (Girl with oranges by Jostein Gaarder) and “Moja droga Aleksandro”(My dear Aleksandra by Krystyna Siesicka), the author analyses the following categories: communicative situation, time variability (experiencing the past, present and future), view point with change ability of focus, perspective change and pronouns, as well as signs of dialogism in texts of literary letters.